Vasopressin therapy in cardiac surgery. Issue 1 (30th December 2018) - Kunkes, Jordan H.; Baker, William L.; Hammond, Jonathan A.; Gluck, Jason
Abstract: Background: Arginine vasopressin (AVP) is a naturally occurring peptide with diverse effects mediated through selective V1 and V2 receptors. About 10% of patients undergoing cardiopulmonary bypass develop postoperative vasodilatory shock requiring high‐dose catecholamines. We sought to examine the role of AVP therapy in cardiac surgery. Methods: A search of Medline was conducted through September 2018 using key words and medical subject headings (MeSH) relating to AVP, copeptin, and cardiac surgery. A systematic review was performed on articles as they pertained to AVP for use as a vasopressor after cardiovascular surgery complicated by vasodilatory shock. Results: A relative or absolute deficiency of Arginine vasopressin is associated with vasodilatory shock after cardiopulmonary bypass. Physiologic replacement with exogenous Arginine vasopressin results in significant increases in systemic vascular resistance and mean arterial pressure with decreased requirements of catecholamines. At doses of <0.1 U/min Arginine vasopressin is safe with very few adverse effects. Conclusion: Post‐cardiopulmonary bypass vasodilatory shock is largely due to a relative deficiency of Arginine vasopressin. Exogenous administration of low‐dose Arginine vasopressin alone or in combination with traditional catecholamines is a safe and effective way to manage this type of vasodilatory shock.